Analysis of tightening sequence effects on preload behaviour of offshore wind turbine M72 bolted connections - Braithwaite, Jarryd; Mehmanparast, Ali (MDPI, 2019)
Offshore wind turbines in shallow waters are predominantly installed using a monopile foundation, onto which a transition piece and wind turbine are attached. Previously, the monopile to transition piece (MP-TP) connection was made using a grouted connection, however, cases of grout failure causing turbine slippage, among other issues, were reported. One solution is to use bolted ring flange connections, which involve using a large number of M72 bolts to provide a firm fixing between the MP-TP. It is in the interest of offshore wind operators to reduce the number of maintenance visits to these wind turbines by maintaining a preload (Fp) level above the minimum requirement for bolted MP-TP connections. The present study focuses on the effect of the tightening sequence on the Fp behaviour of M72 bolted connections. A detailed finite element (FE) model of a seven-bolt, representative segment of a monopile flange was developed with material properties obtained from the available literature. Three analyses were made to examine the effect on Fp after tightening, including the initial Fp level applied to the bolts, the tightening sequence and the effect of an additional tightening pass.
Keywords: bolted connections; tightening sequence; preload